IMPLEMENTASI PROGRAM WORK AND HOLIDAY VISA INDONESIA-AUSTRALIA DALAM KERANGKA IA-CEPA TAHUN 2022-2024 - Athoriq Budiansyah Sallam; Irwan Iskandar (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2026)
The Work and Holiday Visa (WHV) is a collaborative program between Indonesia and Australia that provides young Indonesians with the opportunity to work and vacation in Australia for a specific period. This program is part of the Indonesia-Australia Comprehensive Economic Partnership Agreement (IA-CEPA), which focuses not only on economics and trade but also encompasses human resource development and community mobility. The increasing number of Indonesian participants in the WHV program in the 2022–2024 period indicates that the program is gaining popularity as a means to gain international work experience and enhance personal capacity. This study aims to analyze the implementation of the Indonesia–Australia Work and Holiday Visa program in 2022–2024. The research utilizes a liberal perspective, international cooperation theory, and the nation-state level of analysis. The method used is qualitative research, with data collection through library research. Data were obtained from books, scientific journals, government documents, official reports, and various publications related to the WHV program and the Indonesia–Australia bilateral relationship. The implementation of the WHV program for the 2022–2024 period has seen significant progress, marked by an increase in the number of Indonesian participants following the COVID-19 pandemic. The research results show that the implementation of the Indonesia-Australia Work and Holiday Visa program for the 2022-2024 period has shown positive developments following the COVID-19 pandemic. In its implementation, the Indonesian Government plays a role through the issuance of Work and Holiday Visa Support Letters (SDUWHV) and the participant administrative selection process, while the Australian Government plays a role through the issuance of subclass 462 visas and the regulation of program policies. The implementation of this program provides benefits in improving the quality of Indonesian human resources through international work experience, improved English language skills, and cross-cultural understanding. Thus, the Work and Holiday Visa program is one form of implementation of cooperation between Indonesia and Australia that supports human resource development and strengthens bilateral relations between the two countries. Keywords: Work and Holiday Visa, IA-CEPA, Human Resource Development